Potensi Zat Pengatur Tumbuh Alami Dari Bawang Merah (Allium Cepa L.) Terhadap Perkecambahan Benih Buncis (Phaseolus Vulgaris) - Reza Septa Harita (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the potential of shallot (Allium cepa var. aggregatum) extract as a natural plant growth regulator (PGR) on the germination process of bean seeds (Phaseolus vulgaris L.). The experimental research involved four treatments of shallot extract concentrations: 0% (control), 25%, 50%, and 75%, each using 10 seeds observed over 7 days. The results showed that shallot extract significantly influenced the increase in germinated seeds. The 50% and 75% treatments produced the highest germination rates, reaching 100%, compared to only 70% in the control group. The presence of natural hormones such as auxins and gibberellins in shallots is suspected to accelerate seed physiological activity. Therefore, shallot extract has the potential to serve as an eco-friendly natural alternative to synthetic plant growth regulators in supporting early plant development.